EFEK TERATOGENIK FORMALIN TERHADAP PERKEMBANGAN FETUS MENCIT (Mus musculus) SWISS WEBSTER - Yuli Bahriah Yuli Bahriah (STIKes Budi Mulia Sriwijaya, 2013)
ABSTRACT Formalin was a chemical substance usually added to food production process for preservative. The use of formalin could have a negative impact on health.This thesis aims at knowing teratogenic effect of formalin on the development of fetus mice (Mus musculus) Swiss Webster, that covers the number of life fetus,death fetus and resorption fetus, fetus weight, and also morphology of fetus mice. This thesis was an experimental research with Rancangan Acak Lengkap (RAL) carried out from April to may 2012 at Laboraturium FKIP Biologi Universitas Sriwijaya Palembang. Treatment group was given formalin in a gavage way, while control group is given distilled water. The data would be analyzed using Analysis of Variables (ANOVA). The results showed that giving formalin of about 400 ppm give a significant effect (p>0.05) on the average of life, death, and resorption fetus compared to another treatment dosage on control group. The decrease of fetus weight occurred on any dosage given compared to control group. The difference was significant (abouth p>0.01). Giving formalin has a significant effect (p>0.05) on morphology defect of fetu mice on the dosage given compared to control group. Based on the results of the research it could be concluded that giving formalin to pregnant mice during organogenesis period (6- 15 day of pregnancy) gave teratogenic effect on the development of fetu mice. Giving formalin resulted in the decrease of life fetus, death fetus and embrio of resorption were found on the dosage of about 400 ppm compared to the dosage given to control group. The decrease of fetus weight occurred along with the increase of dosage treatment to control group. The morphology defect of fetus mice found was hemoragi and hematoma of the dosage of 200, 300, and 400 ppm, while the front and rear leg defected and the tail effect accurred on 300 to 400 ppm. ABSTRAK Formalin merupakan salah satu bahan yang biasa ditambahkan untuk bahan pengawet dalam proses produksi makanan. Penggunaan formalin dapat berdampak negatif bagi kesehatan. Penelitian ini bertujuan untuk mengetahui efek teratogenik formalin terhadap perkembangan fetus mencit (Mus musculus) Swiss Webster, yang meliputi jumlah fetus hidup, mati dan resorbsi, berat badan fetus serta morfologi fetus mencit. Penelitian ini merupakan penelitian eksperimen dengan Rancangan Acak Lengkap (RAL) dilakukan pada bulan April sampai Mei 2012 bertempat di Laboratorium FKIP Biologi Universitas Sriwijaya Palembang. Kelompok perlakuan diberi formalin secara gavage, sedangkan kontrol diberi akuades. Data dianalisis dengan uji Analisis of Varians (ANOVA). Hasil penelitian setelah di uji Anova menunjukkan bahwa pemberian formalin pada dosis 400 ppm memberikan pengaruh yang signifikan (p<0,05) terhadap rerata jumlah fetus hidup, mati dan resorbsi dibandingkan dosis perlakuan lain dan kontrol. Penurunan berat badan fetus terjadi pada semua dosis perlakuan formalin dibandingkan kontrol, pengaruhnya berbeda sangat signifikan (p<0,01). Pemberian formalin berpengaruh signifikan (p>0,05) terhadap kelainan/cacat morfologi fetus mencit pada dosis perlakuan dibandingkan kontrol. Berdasarkan hasil penelitian disimpulkan bahwa pemberian formalin terhadap mencit bunting selama masa organogenesis (6-15 hari kebuntingan) memberikan efek teratogenik terhadap perkembangan fetus mencit. Kelainan/cacat morfologi pada fetus mencit yang ditemukan adalah hemoragi dan hematoma pada dosis 200, 300 dan 400 ppm, sedangkan cacat kaki depan, cacat kaki belakang dan cacat ekor pada 300 dan 400 ppm.